From Polders to postmodernism a concise history of archival theory - Ridener, John.; ebrary, Inc. (Duluth, Minn. : Litwin Books, 2009)
"A history of the conception and development of the theories that have guided archivists in their work from the late 19th through the early 21st centuries"--Provided by publisher.
Why study archival theory? -- Contexts -- Consolidation : the Dutch manual -- Confirmation and reinforcement : Sir Hilary Jenkinson's Manual of archive administration -- Modern records : T.R. Schellenberg and modern archives -- Questioning archives : contemporary records, contemporary discourses -- From Polders to postmodernism.
Includes bibliographical references (p. [163]-173) and index.
Electronic reproduction.
Keywords: Archives -- Administration -- History; Archives -- Administration; Electronic books